The effect of low-level estrogen in mandibular bone: An in vivo study - Nike Hendrijanti; Rostiny Rostiny; Mefina Kuntjoro; Hanoem Eka Hidajati; Soekobagiono Soekobagiono; Adi Subianto; Maretaningtias Dwi Ariani; Dika Agung Bakhtiar (Wolters Kluwer Medknow Publications, 2019)
Background: Low levels of estrogen can cause osteoporosis and usually occur during a woman's menopausal phase. Osteoporosis can lead to bone resorption, the absence of osseointegration, and implant failure. The aim of this study is to determine the expression of transforming growth factor-beta 1 (TGF-β1), runt-related transcription factor (RUNX2), and osteoblasts in mandibular rats with low levels of estrogen. Materials and Methods: This study is an in vivo experimental research. Female Wistar rats (n = 18) were divided into two groups: (1) Postsham surgery and (2) ovariectomy group. After 12 weeks, the rats were sacrificed to identify the level of estrogen, while histological analysis was conducted to determine the level of osteoblast and the expression of TGF-β1 and RUNX2. The data were analyzed using t-test (P < 0.05). Results: There were significant lower levels of estrogen and osteoblast among the ovariectomy group compared to the postsham group (P < 0.05). RUNX2 levels were found to be significantly higher in the ovariectomy group than that in the postsham group (P < 0.05). However, there were no significant differences between TGF-β1 levels within the ovariectomy and postsham groups (P > 0.05). Conclusion: Ovariectomy can lead to decreased osteoblastogenesis in mandibular bone by the reduced level of osteoblast and the increased expression of TGF-β1 and RUNX2.